Super-stain-resistant travertine grain PVC coiled material and production process thereof
Through specific formulas and processes, the PVC rolls of super dirt -resistant cave stone patterns are prepared, which solves the lack of traditional PVC materials in terms of dirt resistance and weather resistance, and realizes the significant improvement of the weather resistance and stain resistance of the materials, and it will also improve the significant improvement of materials and stain resistance. Simulates the texture and texture of natural cave stones, and is suitable for high -end decoration fields.
Patent Information
- Application Number
- CN202411687373.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-01-24
AI Technical Summary
Traditional PVC decorative materials have shortcomings in terms of stain resistance and weather resistance, which limits their application in high-end decoration fields, and the market demand for decorative materials with natural stone texture and texture is growing.
Through specific formulas and processes, prepare ultra -dirt -resistant cave stone pattern PVC coils, and use PVC resin, thermal stabilizer, plasticizer, lubricant, sulfur, filler, dark and light color pigment and other materials, combined with double cone And single screw extrusion process, temperature control, pressure extension technology, and secondary vulcanization treatment, simulate the texture and texture of natural cave stones, and paint the modified polyurethane coatings on the surface to improve the weather resistance and stain resistance.
It significantly improves the dirt resistance and weather resistance of PVC coils, makes stains more difficult to attach and easier to clean, extend the service life of the product, and approach natural stone in terms of visual effects, which improves the decorative effect.
Smart Images

Figure BDA0005149946170000191 
Figure BDA0005149946170000192
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, and in particular to a super-fouling-resistant travertine-grain PVC coil and a production process thereof. Background Art
[0002] With the rapid development of the construction industry and interior decoration, the performance requirements for decorative materials are getting higher and higher. Especially in the fields of commercial buildings, home decoration and public facilities, there are strict requirements for the aesthetics, durability and ease of maintenance of materials. As an economical and practical material, polyvinyl chloride (PVC) occupies an important position in the decorative materials market due to its lightness, durability and easy processing. However, traditional PVC decorative materials have shortcomings in terms of stain resistance and weather resistance, which limits its application in high-end decoration fields.
[0003] In the existing technology, the improvement of the stain resistance and weather resistance of PVC materials mainly depends on the addition of various additives and coatings. For example, by adding specific stabilizers, plasticizers and lubricants, the processing performance and service life of PVC materials can be improved. In addition, by coating a protective layer such as polyurethane coating on the surface of PVC, its stain resistance and weather resistance can be enhanced. However, these methods often have certain limitations, such as insufficient adhesion between the coating and the substrate, poor weather resistance of the coating, or insufficient hardness and wear resistance of the coating, resulting in the gradual degradation of the decorative effect over time.
[0004] In addition, there is a growing demand for decorative materials with natural stone texture and feel. Travertine, as a natural stone, is favored for its unique texture and aesthetics. However, the mining and processing costs of natural travertine are high and it is non-renewable. Therefore, developing a PVC coil with travertine texture and feel as well as excellent stain resistance and weather resistance is of great significance to meet the market demand.
[0005] Chinese invention patent CN106554581A discloses a polyvinyl chloride waterproofing coil and its preparation method, which belongs to the field of polymer materials. It is characterized by being composed of a polyvinyl chloride composition waterproofing layer on the outer layer and a skeleton reinforcement layer of polyvinyl chloride fiber textiles on the inner layer. After the materials are mixed, a process of extrusion and calendering is adopted by multiple extruders to make the upper and lower layers of the coil and the interlayer of polyvinyl chloride fiber textiles into polyvinyl chloride composition layers, the extrusion temperature is 160℃~190℃, and the setting temperature is 180℃~210℃. In this invention, chlorinated nylon textiles are used as reinforcing materials, which improve the strength of PVC waterproofing coil while having flame retardant properties; chlorinated nylon textiles have similar properties to PVC waterproofing layers and do not require surface treatment when used; the coil of this invention has good durability and is easy to recycle. However, the weather resistance and stain resistance of the polyvinyl chloride waterproofing coil prepared by this invention need to be improved. Summary of the invention
[0006] In view of the above problems, the present invention aims to provide a super-fouling resistant travertine-patterned PVC coil and a production process thereof. Through a specific formula and process, the PVC coil can not only simulate the texture and feel of natural travertine, but also has significant improvements in stain resistance and weather resistance, thereby broadening the application scope of PVC materials in the field of high-end decorative materials.
[0007] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:
[0008] A production process of a super stain-resistant travertine-grain PVC coil is as follows, in parts by weight:
[0009] Step 1, 60-80 parts of PVC resin, 4-6 parts of heat stabilizer, 8-12 parts of plasticizer, 0.2-0.4 parts of lubricant, 0.5-0.7 parts of sulfur, 2-4 parts of filler, 2-4 parts of dark pigment and 2-4 parts of light pigment are mixed evenly, and the mixing temperature is adjusted to 80-120° C. to obtain dark raw material and light raw material respectively;
[0010] Step 2, adding 80-120 parts of the dark raw material and 60-100 parts of the light raw material prepared in step 1 to two double-cone extruders respectively, extruding them by conventional extrusion process, and adding the extruded raw materials together to a single screw extruder; extruding by conventional extrusion process, the extruded raw materials are cut into soft pellets with a diameter of 8-12 mm and a length of 3-4 mm;
[0011] Step 3, the soft pellets prepared in step 2 are immediately put into a closed heating conveyor belt to ensure that the temperature of the pellets is maintained at 155-160°C; the pellets quickly enter the mixing mill through the conveyor belt; the roller distance of the mixing mill is controlled at 2-5mm, the temperature of the front roller is controlled at 160-180°C, the temperature of the rear roller is 140-160°C, and the speed ratio of the front and rear rollers is 0.6-0.9 to obtain refined materials;
[0012] Step 4, adding 8 to 12 parts of transparent PVC particles to the refined material prepared in step 3 before the calender, and calendering to obtain a calendered material;
[0013] Step 5, performing secondary vulcanization treatment on the calendered material prepared in step 4, and cooling to room temperature after the secondary vulcanization treatment is completed so that the edges of the holes become flat, thereby obtaining a vulcanized material;
[0014] Step 6: Apply modified polyurethane coating on the surface of the vulcanized material prepared in step 5, with the total coating amount on both sides being 60-100 g / m 2 , and then drying at 80-110°C at a drying speed of 10-15m / min to obtain a super-fouling resistant travertine-grain PVC coil.
[0015] The dark pigment is one or two of black iron oxide, aniline black, carbon black, antimony sulfide, and red iron oxide; the light pigment is titanium white.
[0016] The heat stabilizer includes one or more of a calcium zinc stabilizer, a barium zinc stabilizer, and an organic tin stabilizer.
[0017] The plasticizer includes one or more of dioctyl phthalate, dioctyl terephthalate, trioctyl trimellitate, polypropylene adipate, epoxy soybean oil, and trioctyl trimellitate.
[0018] The lubricant includes one or more of paraffin wax, monoglyceride, and polyethylene wax;
[0019] The filler includes one or more of light calcium carbonate and heavy calcium carbonate.
[0020] The calender in step 4 is a five-roll calender, and the sheet forming parameters of the five-roll calender are: the temperature of the 1# roller is controlled at 180-200°C and the speed is 18-22rpm; the temperature of the 2# roller is controlled at 180-200°C and the speed is 20-24rpm; the temperature of the 3# roller is controlled at 190-200°C and the speed is 23-27rpm; the temperature of the 4# roller is controlled at 180-220°C and the speed is 25-28rpm; the temperature of the 5# roller is controlled at 180-190°C and the speed is 28-32rpm.
[0021] The vulcanization treatment in step 5 is to hot-press the mixed material on a flat vulcanizer at 170-190° C. for 20-40 minutes.
[0022] The preparation method of the modified polyurethane coating is as follows, in parts by weight:
[0023] S1. Mix and stir 18 to 22 parts of polycarbonate diol, 13 to 18 parts of 3-ethylheptamethyltrisiloxane and 18 to 22 parts of 1,6-hexamethylene diisocyanate, heat to 70 to 80°C, add 0.2 to 0.4 parts of dibutyltin dilaurate, treat for 1 to 3 hours, cool to 40 to 55°C, add 0.5 to 2 parts of neopentyl glycol, 1 to 1.5 parts of 2,2-bis(hydroxymethyl)malonic acid and 0.5 to 1 part of acetone, treat for 4 to 8 minutes, heat to 70 to 80°C again, continue to treat for 1 to 5 hours, then add 5 to 7 parts of acrylic resin, treat at 70 to 80°C for 1 to 2 hours, after the reaction is completed, cool to 40 to 60°C, add 1 to 3 parts of triethylamine, treat for 30 to 50 minutes, finally add 20 to 40 parts of water and stir for 0.1 to 1 hour to obtain a pretreated product;
[0024] S2, 0.02-0.06 parts of dihexadecyl dimethyl ammonium bromide, 8-12 parts of water, 5-6 parts of anhydrous ethanol and 0.2-0.3 parts of 20-26wt% ammonia water are mixed, and while stirring, 0.1-0.2 parts of ethyl orthosilicate and 0.05-0.1 parts of 3-methacryloxypropyl tri(isopropyleneoxy)silane are gradually added, the mixture is heated to 50-60°C, and treated for 12-48 hours. After the treatment, centrifugation is performed at a speed of 3000-8000 rpm for 3-10 minutes, and washing is performed with water and ethanol for 1-3 times respectively, and vacuum drying is performed at 50-65°C for 5-10 hours to obtain a modified compound;
[0025] S3, the modified compound prepared in step S2 is mixed and dispersed with 8 to 12 parts of 70 to 85 wt % ethanol aqueous solution, and then ground for 5 to 15 hours to prepare a slurry, the slurry is mixed with the pretreated material prepared in step S1, 0.4 to 0.6 parts of sodium citrate and 0.1 to 0.3 parts of sodium persulfate, and ultrasonicated for 0.5 to 2 hours at an ultrasonic power of 200 to 400 W and an ultrasonic frequency of 20 to 60 kHz to obtain a modified polyurethane coating.
[0026] Preferably, the preparation method of the modified polyurethane coating is as follows, in parts by weight:
[0027] S1. Mix and stir 18 to 22 parts of polycarbonate diol, 13 to 18 parts of 3-ethylheptamethyltrisiloxane and 18 to 22 parts of 1,6-hexamethylene diisocyanate, heat to 70 to 80°C, add 0.2 to 0.4 parts of dibutyltin dilaurate, treat for 1 to 3 hours, cool to 40 to 55°C, add 0.5 to 2 parts of neopentyl glycol, 1 to 1.5 parts of 2,2-bis(hydroxymethyl)malonic acid and 0.5 to 1 part of acetone, treat for 4 to 8 minutes, heat to 70 to 80°C again, continue to treat for 1 to 5 hours, then add 5 to 7 parts of acrylic resin, treat at 70 to 80°C for 1 to 2 hours, after the reaction is completed, cool to 40 to 60°C, add 1 to 3 parts of triethylamine, treat for 30 to 50 minutes, finally add 20 to 40 parts of water and stir for 0.1 to 1 hour to obtain a pretreated product;
[0028] S2, 0.02-0.06 parts of dihexadecyl dimethyl ammonium bromide, 8-12 parts of water, 5-6 parts of anhydrous ethanol and 0.2-0.3 parts of 20-26wt% ammonia water are mixed, and while stirring, 0.1-0.2 parts of ethyl orthosilicate and 0.03-0.05 parts of 3-methacryloxypropyl tris(isopropyleneoxy)silane and 0.03-0.05 parts of methacryloxypropyl tris(trimethylsiloxy)silane are gradually added, and the mixture is heated to 50-60°C and treated for 12-48 hours. After the treatment, the mixture is centrifuged at a speed of 3000-8000 rpm for 3-10 minutes, and washed with water and ethanol for 1-3 times respectively, and vacuum dried at 50-65°C for 5-10 hours to obtain a modified compound;
[0029] S3, the modified compound prepared in step S2 is mixed and dispersed with 8 to 12 parts of 70 to 85 wt % ethanol aqueous solution, and then ground for 5 to 15 hours to prepare a slurry, the slurry is mixed with the pretreated material prepared in step S1, 0.4 to 0.6 parts of sodium citrate and 0.1 to 0.3 parts of sodium persulfate, and ultrasonicated for 0.5 to 2 hours at an ultrasonic power of 200 to 400 W and an ultrasonic frequency of 20 to 60 kHz to obtain a modified polyurethane coating.
[0030] Further preferably, the preparation method of the modified polyurethane coating is as follows, in parts by weight:
[0031] S1. Mix and stir 18 to 22 parts of polycarbonate diol, 13 to 18 parts of 3-ethylheptamethyltrisiloxane and 18 to 22 parts of 1,6-hexamethylene diisocyanate, heat to 70 to 80°C, add 0.2 to 0.4 parts of dibutyltin dilaurate, treat for 1 to 3 hours, cool to 40 to 55°C, add 0.5 to 2 parts of neopentyl glycol, 1 to 1.5 parts of 1,1-cyclopropyldicarboxylic acid and 0.5 to 1 part of acetone, treat for 4 to 8 minutes, heat to 70 to 80°C again, continue to treat for 1 to 5 hours, then add 5 to 7 parts of acrylic resin, treat at 70 to 80°C for 1 to 2 hours, after the reaction is completed, cool to 40 to 60°C, add 1 to 3 parts of triethylamine, treat for 30 to 50 minutes, finally add 20 to 40 parts of water and stir for 0.1 to 1 hour to obtain a pretreated product;
[0032] S2, 0.02-0.06 parts of dihexadecyl dimethyl ammonium bromide, 8-12 parts of water, 5-6 parts of anhydrous ethanol and 0.2-0.3 parts of 20-26wt% ammonia water are mixed, and while stirring, 0.1-0.2 parts of ethyl orthosilicate and 0.03-0.05 parts of 3-methacryloxypropyl tris(isopropyleneoxy)silane and 0.03-0.05 parts of methacryloxypropyl tris(trimethylsiloxy)silane are gradually added, and the mixture is heated to 50-60°C and treated for 12-48 hours. After the treatment, the mixture is centrifuged at a speed of 3000-8000 rpm for 3-10 minutes, and washed with water and ethanol for 1-3 times respectively, and vacuum dried at 50-65°C for 5-10 hours to obtain a modified compound;
[0033] S3, the modified compound prepared in step S2 is mixed and dispersed with 8 to 12 parts of 70 to 85 wt % ethanol aqueous solution, and then ground for 5 to 15 hours to prepare a slurry, the slurry is mixed with the pretreated material prepared in step S1, 0.4 to 0.6 parts of sodium citrate and 0.1 to 0.3 parts of sodium persulfate, and ultrasonicated for 0.5 to 2 hours at an ultrasonic power of 200 to 400 W and an ultrasonic frequency of 20 to 60 kHz to obtain a modified polyurethane coating.
[0034] In the production process of the super stain-resistant travertine-grain PVC coil of the present invention, the functions of various substances are as follows:
[0035] PVC resin is the base material of the coil and provides the main structure and physical properties.
[0036] Calcium zinc stabilizer is used to maintain the thermal stability of PVC resin during processing to prevent decomposition.
[0037] Dioctyl phthalate acts as a plasticizer to increase the flexibility and processability of PVC.
[0038] Polyethylene wax acts as a lubricant to reduce friction and improve fluidity of materials during processing.
[0039] Sulfur, as a vulcanizing agent, improves the heat resistance and aging resistance of PVC.
[0040] Light calcium carbonate is used as a filler to increase the volume of PVC, improve mechanical properties and reduce costs.
[0041] Carbon black acts as a dark pigment, providing color and UV protection.
[0042] Titanium white is used as a light pigment to provide a white effect, increase brightness and hiding power.
[0043] Transparent PVC particles are added to the material to imitate the highly transparent quartz component in travertine, increasing the transparency and aesthetics of the product.
[0044] Modified polyurethane coatings are used as surface coatings to provide stain resistance, weather resistance and decorative effects.
[0045] In the preparation of modified polyurethane coatings:
[0046] As the polyol component of polyurethane coatings, polycarbonate diols affect the flexibility and wear resistance of the coatings.
[0047] 3-Ethylheptamethyltrisiloxane is used as a siloxane component to improve the weather resistance and water resistance of the coating.
[0048] As an isocyanate component, 1,6-hexamethylene diisocyanate participates in the polymerization reaction of polyurethane to form the main structure of the coating.
[0049] Dibutyltin dilaurate is used as a catalyst to accelerate the curing reaction of polyurethane coatings.
[0050] Neopentyl glycol, as an active small molecule diol, participates in the cross-linking reaction of the coating.
[0051] 2,2-Bis(hydroxymethyl)malonic acid increases the crosslinking density and hardness of the coating.
[0052] Acetone reduces the viscosity of the coating, making it easier to mix and apply.
[0053] Acrylic resins improve the weather resistance and adhesion of coatings.
[0054] Triethylamine promotes crosslinking and curing of the coating.
[0055] Dihexadecyl dimethyl ammonium bromide improves the dispersion and stability of coatings.
[0056] Tetraethyl orthosilicate is used as a siloxane coupling agent to enhance the adhesion between the coating and the substrate.
[0057] 3-Methacryloxypropyltri(isopropenyloxy)silane and methacryloxypropyltri(trimethylsiloxy)silane act as modified silanes to provide the coating with hydrophobicity and stain resistance.
[0058] Sodium citrate and sodium persulfate are used as stabilizers and initiators for coatings to improve the stability and curing properties of coatings.
[0059] Compared with the prior art, it has the following beneficial effects:
[0060] 1) The present invention significantly improves the stain resistance of the product by coating the modified polyurethane coating on the surface of the PVC coil, making it more difficult for stains to adhere and easier to clean, thereby improving the practicality and aesthetics of the material.
[0061] 2) The present invention adopts a specific production process and raw material ratio. The PVC coiled material prepared by the present invention exhibits excellent weather resistance, can maintain stable performance under various climatic conditions, and prolongs the service life of the product.
[0062] 3) The present invention can simulate the natural soft texture and highly transparent quartz component of natural travertine by precisely controlling the production process, making the PVC coil closer to natural stone in visual effect and improving the decorative effect. DETAILED DESCRIPTION
[0063] Main sources of substances:
[0064] PVC resin, from Qilu Petrochemical, brand S-800.
[0065] Calcium zinc stabilizer was purchased from Kunshan Meijisen Composite Materials Co., Ltd., model: CZ75.
[0066] Transparent PVC particles, brand: S03, Cixi Aode Plastic Industry Co., Ltd.
[0067] Polyethylene wax, Q-400, was purchased from Wuhan Xindongyi Chemical Co., Ltd.
[0068] Polycarbonate diol, Brand: Brand: C1200.
[0069] Acrylic resin, Dynacoll AC1630, was purchased from Evonik Specialty Chemicals (Shanghai) Co., Ltd.
[0070] Sulfur, product number: S200, was purchased from Chaoyang Mingyu Chemical Co., Ltd.
[0071] Light calcium carbonate, particle size: 1250 mesh, item number: 001, from Lingshou County Baofeng Mica Processing Co., Ltd.
[0072] Carbon black, model: N330, Tianjin Yiborui Chemical Co., Ltd.
[0073] Titanium dioxide, rutile type, was purchased from Shanghai Yuejiang Titanium Dioxide Chemical Products Co., Ltd.
[0074] The remaining raw materials in the examples and comparative examples of the present invention are all commercially available products.
[0075] The design idea of the present invention is to prepare a PVC coil with super stain-resistant travertine effect by combining a specific PVC resin ratio, pigment selection, double-cone and single-screw extrusion process, temperature control, calendering molding technology and secondary vulcanization treatment, and coat a modified polyurethane coating on the surface to enhance its weather resistance and stain resistance, thereby providing a new polymer material that is both beautiful and practical.
[0076] Example 1
[0077] The production process of a super stain-resistant travertine-grain PVC coil is as follows:
[0078] Step 1, 70kg of PVC resin, 5kg of calcium zinc stabilizer, 10kg of dioctyl phthalate, 0.3kg of polyethylene wax, 0.6kg of sulfur, 3kg of light calcium carbonate, 3kg of carbon black and 3kg of titanium dioxide are mixed evenly, and the mixing temperature is adjusted to 100° C. to obtain dark raw materials and light raw materials respectively;
[0079] Step 2, adding 100 kg of dark raw material and 80 kg of light raw material prepared in step 1 to two double-cone extruders respectively, extruding by conventional extrusion process, and adding the extruded raw materials together to a single screw extruder; extruding by conventional extrusion process, the extruded raw materials are cut into soft pellets with a diameter of 10 mm and a length of 3.5 mm;
[0080] Step 3, the soft pellets prepared in step 2 are immediately put into a closed heating conveyor belt to ensure that the temperature of the pellets is maintained at 158°C; the pellets quickly enter the open mill through the conveyor belt; the roller spacing of the open mill is controlled at 4mm, the temperature of the front roller is controlled at 170°C, the temperature of the rear roller is 150°C, and the speed ratio of the front and rear rollers is 0.8 to obtain refined materials, and the shear force generated by the temperature difference and speed difference of the front and rear rollers is used to form a natural and soft texture on the surface of the refined material after forming, which is very close to the natural high-end travertine; by adjusting the mass ratio of dark raw materials and light raw materials, the thickness and depth of the surface texture can be arbitrarily modulated; due to the certain proportion of water contained in the material, small holes of different sizes and depths will be formed during the extrusion and calendering process, imitating the hole structure on the surface of travertine;
[0081] Step 4: Add the refined material prepared in step 3 to 10kg of transparent PVC particles before the calender, so that the molded product also has irregular transparent points, imitating the high transparent quartz component in the travertine. The sheet molding parameters of the five-roll calender are: 1# roller temperature is controlled at 190°C and speed is 20rpm; 2# roller temperature is controlled at 190°C and speed is 22rpm; 3# roller temperature is controlled at 195°C and speed is 25rpm; 4# roller temperature is controlled at 200°C and speed is 27rpm; 5# roller temperature is controlled at 185°C and speed is 30rpm, and the calendered material is obtained;
[0082] Step 5, performing secondary vulcanization treatment on the calendered material prepared in step 4, wherein the mixed material is hot-pressed on a flat vulcanizer at 180° C. for 30 minutes, and after the secondary vulcanization treatment is completed, the mixed material is cooled to room temperature so that the edges of the holes become flat, thereby obtaining a vulcanized material;
[0083] Step 6: Apply modified polyurethane coating on the surface of the vulcanized material prepared in step 5, with a total coating amount of 80 g / m 2 , and then dried at 100°C at a drying speed of 12m / min to obtain a super stain-resistant travertine-grain PVC coil.
[0084] The preparation method of the modified polyurethane coating is as follows:
[0085] S1, 20kg polycarbonate diol, 15kg 3-ethyl heptamethyl trisiloxane and 20kg 1,6-hexamethylene diisocyanate were mixed and stirred, heated to 75°C, 0.3kg dibutyltin dilaurate was added, and after treating for 1.5 hours, the temperature was lowered to 50°C, 1kg neopentyl glycol, 1.2kg 2,2-bis(hydroxymethyl)malonic acid and 0.8kg acetone were added, and the temperature was raised to 75°C again after treating for 6 minutes, and the treatment was continued for 3 hours, and then 6kg acrylic resin was added, and the treatment was carried out at 75°C for 1.5 hours. After the reaction was completed, the temperature was lowered to 50°C, 2kg triethylamine was added, and the treatment was carried out for 40 minutes, and finally 30kg water was added and stirred for 0.5 hours to obtain a pretreated product;
[0086] S2, 0.04 kg of dihexadecyl dimethyl ammonium bromide, 10 kg of water, 5.6 kg of anhydrous ethanol and 0.28 kg of 25 wt% ammonia water were mixed, and 0.15 kg of ethyl orthosilicate and 0.08 kg of 3-methacryloxypropyltri(isopropenyloxy)silane were gradually added while stirring, and the mixture was heated to 55° C. and treated for 24 hours. After the treatment, the mixture was centrifuged at a speed of 5000 rpm for 5 minutes, and washed twice with water and ethanol respectively, and vacuum dried at 60° C. for 8 hours to obtain a modified compound;
[0087] S3, the modified compound prepared in step S2 is mixed and dispersed with 10 kg of 80 wt% ethanol aqueous solution, and then ground for 10 hours to prepare a slurry, the slurry is mixed with the pretreated material prepared in step S1, 0.5 kg of sodium citrate and 0.2 kg of sodium persulfate, and ultrasonicated for 1 hour at an ultrasonic power of 300 W and an ultrasonic frequency of 40 kHz to obtain a modified polyurethane coating.
[0088] Example 2
[0089] The production process of a super stain-resistant travertine-grain PVC coil is basically the same as that of Example 1, with the only difference being the preparation method of the modified polyurethane coating being different.
[0090] The preparation method of the modified polyurethane coating is as follows:
[0091] S1, 20kg polycarbonate diol, 15kg 3-ethyl heptamethyl trisiloxane and 20kg 1,6-hexamethylene diisocyanate were mixed and stirred, heated to 75°C, 0.3kg dibutyltin dilaurate was added, and after treating for 1.5 hours, the temperature was lowered to 50°C, 1kg neopentyl glycol, 1.2kg 2-methyl-3-hydroxypropionic acid and 0.8kg acetone were added, and the temperature was raised to 75°C again after treating for 6 minutes, and the treatment was continued for 3 hours, and then 6kg acrylic resin was added, and the treatment was carried out at 75°C for 1.5 hours. After the reaction was completed, the temperature was lowered to 50°C, 2kg triethylamine was added, and the treatment was carried out for 40 minutes, and finally 30kg water was added and stirred for 0.5 hours to obtain a pretreated product;
[0092] S2, 0.04 kg of dihexadecyl dimethyl ammonium bromide, 10 kg of water, 5.6 kg of anhydrous ethanol and 0.28 kg of 25 wt% ammonia water were mixed, and 0.15 kg of ethyl orthosilicate and 0.08 kg of 3-methacryloxypropyltri(isopropenyloxy)silane were gradually added while stirring, and the mixture was heated to 55° C. and treated for 24 hours. After the treatment, the mixture was centrifuged at a speed of 5000 rpm for 5 minutes, and washed twice with water and ethanol respectively, and vacuum dried at 60° C. for 8 hours to obtain a modified compound;
[0093] S3, the modified compound prepared in step S2 is mixed and dispersed with 10 kg of 80 wt% ethanol aqueous solution, and then ground for 10 hours to prepare a slurry, the slurry is mixed with the pretreated material prepared in step S1, 0.5 kg of sodium citrate and 0.2 kg of sodium persulfate, and ultrasonicated for 1 hour at an ultrasonic power of 300 W and an ultrasonic frequency of 40 kHz to obtain a modified polyurethane coating.
[0094] Example 3
[0095] The production process of a super stain-resistant travertine-grain PVC coil is basically the same as that of Example 1, with the only difference being the preparation method of the modified polyurethane coating being different.
[0096] The preparation method of the modified polyurethane coating is as follows:
[0097] S1, 20kg polycarbonate diol, 15kg 3-ethyl heptamethyl trisiloxane and 20kg 1,6-hexamethylene diisocyanate were mixed and stirred, heated to 75°C, 0.3kg dibutyltin dilaurate was added, and after treating for 1.5 hours, the temperature was lowered to 50°C, 1kg neopentyl glycol, 1.2kg 2,2-dimethyl-3-hydroxypropionic acid and 0.8kg acetone were added, and the temperature was raised to 75°C again after treating for 6 minutes, and the treatment was continued for 3 hours, and then 6kg acrylic resin was added, and the treatment was carried out at 75°C for 1.5 hours. After the reaction was completed, the temperature was lowered to 50°C, 2kg triethylamine was added, and the treatment was carried out for 40 minutes, and finally 30kg water was added and stirred for 0.5 hours to obtain a pretreated product;
[0098] S2, 0.04 kg of dihexadecyl dimethyl ammonium bromide, 10 kg of water, 5.6 kg of anhydrous ethanol and 0.28 kg of 25 wt% ammonia water were mixed, and 0.15 kg of ethyl orthosilicate and 0.08 kg of 3-methacryloxypropyltri(isopropenyloxy)silane were gradually added while stirring, and the mixture was heated to 55° C. and treated for 24 hours. After the treatment, the mixture was centrifuged at a speed of 5000 rpm for 5 minutes, and washed twice with water and ethanol respectively, and vacuum dried at 60° C. for 8 hours to obtain a modified compound;
[0099] S3, the modified compound prepared in step S2 is mixed and dispersed with 10 kg of 80 wt% ethanol aqueous solution, and then ground for 10 hours to prepare a slurry, the slurry is mixed with the pretreated material prepared in step S1, 0.5 kg of sodium citrate and 0.2 kg of sodium persulfate, and ultrasonicated for 1 hour at an ultrasonic power of 300 W and an ultrasonic frequency of 40 kHz to obtain a modified polyurethane coating.
[0100] Example 4
[0101] The production process of a super stain-resistant travertine-grain PVC coil is basically the same as that of Example 1, with the only difference being the preparation method of the modified polyurethane coating being different.
[0102] The preparation method of the modified polyurethane coating is as follows:
[0103] S1, 20kg polycarbonate diol, 15kg 3-ethyl heptamethyl trisiloxane and 20kg 1,6-hexamethylene diisocyanate were mixed and stirred, heated to 75°C, 0.3kg dibutyltin dilaurate was added, and after treating for 1.5 hours, the temperature was lowered to 50°C, 1kg neopentyl glycol, 1.2kg 2,2-bis(hydroxymethyl)malonic acid and 0.8kg acetone were added, and the temperature was raised to 75°C again after treating for 6 minutes, and the treatment was continued for 3 hours, and then 6kg acrylic resin was added, and the treatment was carried out at 75°C for 1.5 hours. After the reaction was completed, the temperature was lowered to 50°C, 2kg triethylamine was added, and the treatment was carried out for 40 minutes, and finally 30kg water was added and stirred for 0.5 hours to obtain a pretreated product;
[0104] S2, 0.04 kg of dihexadecyl dimethyl ammonium bromide, 10 kg of water, 5.6 kg of anhydrous ethanol and 0.28 kg of 25 wt% ammonia water were mixed, and 0.15 kg of ethyl orthosilicate and 0.08 kg of methacryloxypropyl tris(trimethylsiloxy)silane were gradually added while stirring, and the mixture was heated to 55 ° C. and treated for 24 hours. After the treatment, it was centrifuged at a speed of 5000 rpm for 5 minutes, and washed twice with water and ethanol respectively, and vacuum dried at 60 ° C. for 8 hours to obtain a modified compound;
[0105] S3, the modified compound prepared in step S2 is mixed and dispersed with 10 kg of 80 wt% ethanol aqueous solution, and then ground for 10 hours to prepare a slurry, the slurry is mixed with the pretreated material prepared in step S1, 0.5 kg of sodium citrate and 0.2 kg of sodium persulfate, and ultrasonicated for 1 hour at an ultrasonic power of 300 W and an ultrasonic frequency of 40 kHz to obtain a modified polyurethane coating.
[0106] Example 5
[0107] The production process of a super stain-resistant travertine-grain PVC coil is basically the same as that of Example 1, with the only difference being the preparation method of the modified polyurethane coating being different.
[0108] The preparation method of the modified polyurethane coating is as follows:
[0109] S1, 20kg polycarbonate diol, 15kg 3-ethyl heptamethyl trisiloxane and 20kg 1,6-hexamethylene diisocyanate were mixed and stirred, heated to 75°C, 0.3kg dibutyltin dilaurate was added, and after treating for 1.5 hours, the temperature was lowered to 50°C, 1kg neopentyl glycol, 1.2kg 2,2-bis(hydroxymethyl)malonic acid and 0.8kg acetone were added, and the temperature was raised to 75°C again after treating for 6 minutes, and the treatment was continued for 3 hours, and then 6kg acrylic resin was added, and the treatment was carried out at 75°C for 1.5 hours. After the reaction was completed, the temperature was lowered to 50°C, 2kg triethylamine was added, and the treatment was carried out for 40 minutes, and finally 30kg water was added and stirred for 0.5 hours to obtain a pretreated product;
[0110] S2, 0.04 kg of dihexadecyl dimethyl ammonium bromide, 8 kg of water, 5.6 kg of anhydrous ethanol and 0.28 kg of 25 wt% ammonia water were mixed, and while stirring, 0.15 kg of ethyl orthosilicate and 0.08 kg of bis-3-methylpropyleneoxypropylated tetramethyldisiloxane were gradually added, and the mixture was heated to 55 ° C and treated for 24 hours. After the treatment, it was centrifuged at a speed of 5000 rpm for 5 minutes, and washed twice with water and ethanol respectively, and vacuum dried at 60 ° C for 8 hours to obtain a modified compound;
[0111] S3, the modified compound prepared in step S2 is mixed and dispersed with 10 kg of 80 wt% ethanol aqueous solution, and then ground for 10 hours to prepare a slurry, the slurry is mixed with the pretreated material prepared in step S1, 0.5 kg of sodium citrate and 0.2 kg of sodium persulfate, and ultrasonicated for 1 hour at an ultrasonic power of 300 W and an ultrasonic frequency of 40 kHz to obtain a modified polyurethane coating.
[0112] Example 6
[0113] The production process of a super stain-resistant travertine-grain PVC coil is basically the same as that of Example 1, with the only difference being the preparation method of the modified polyurethane coating being different.
[0114] The preparation method of the modified polyurethane coating is as follows:
[0115] S1, 20kg polycarbonate diol, 15kg 3-ethyl heptamethyl trisiloxane and 20kg 1,6-hexamethylene diisocyanate were mixed and stirred, heated to 75°C, 0.3kg dibutyltin dilaurate was added, and after treating for 1.5 hours, the temperature was lowered to 50°C, 1kg neopentyl glycol, 1.2kg 2,2-bis(hydroxymethyl)malonic acid and 0.8kg acetone were added, and the temperature was raised to 75°C again after treating for 6 minutes, and the treatment was continued for 3 hours, and then 6kg acrylic resin was added, and the treatment was carried out at 75°C for 1.5 hours. After the reaction was completed, the temperature was lowered to 50°C, 2kg triethylamine was added, and the treatment was carried out for 40 minutes, and finally 30kg water was added and stirred for 0.5 hours to obtain a pretreated product;
[0116] S2, 0.04kg of dihexadecyl dimethyl ammonium bromide, 10kg of water, 5.6kg of anhydrous ethanol and 0.28kg of 25wt% ammonia water were mixed, and while stirring, 0.15kg of ethyl orthosilicate and 0.04kg of 3-methacryloxypropyl tris(isopropenyloxy)silane and 0.04kg of methacryloxypropyl tris(trimethylsiloxy)silane were gradually added, and the mixture was heated to 55°C and treated for 24 hours. After the treatment, the mixture was centrifuged at a speed of 5000rpm for 5 minutes, washed twice with water and ethanol respectively, and vacuum dried at 60°C for 8 hours to obtain a modified compound;
[0117] S3, the modified compound prepared in step S2 is mixed and dispersed with 10 kg of 80 wt% ethanol aqueous solution, and then ground for 10 hours to prepare a slurry, the slurry is mixed with the pretreated material prepared in step S1, 0.5 kg of sodium citrate and 0.2 kg of sodium persulfate, and ultrasonicated for 1 hour at an ultrasonic power of 300 W and an ultrasonic frequency of 40 kHz to obtain a modified polyurethane coating.
[0118] Example 7
[0119] The method is substantially the same as Example 6, except that 2,2-bis(hydroxymethyl)malonic acid is replaced with an equal mass of 1,1-cyclopropyldicarboxylic acid.
[0120] Comparative Example 1
[0121] The production process of a super stain-resistant travertine-grain PVC coil is basically the same as that of Example 1, with the only difference being the preparation method of the modified polyurethane coating being different.
[0122] The preparation method of the modified polyurethane coating is as follows:
[0123] S1, 20kg polycarbonate diol, 15kg 3-ethyl heptamethyl trisiloxane and 20kg 1,6-hexamethylene diisocyanate were mixed and stirred, heated to 75°C, 0.3kg dibutyltin dilaurate was added, and after treating for 1.5 hours, the temperature was lowered to 50°C, 1kg neopentyl glycol, 1.2kg 2,2-bishydroxymethyl propionic acid and 0.8kg acetone were added, and the temperature was raised to 75°C again after treating for 6 minutes, and the treatment was continued for 3 hours, and then 6kg acrylic resin was added, and the treatment was carried out at 75°C for 1.5 hours. After the reaction was completed, the temperature was lowered to 50°C, 2kg triethylamine was added, and the treatment was carried out for 40 minutes, and finally 30kg water was added and stirred for 0.5 hours to obtain a pretreated product;
[0124] S2, 0.04 kg of dihexadecyl dimethyl ammonium bromide, 10 kg of water, 5.6 kg of anhydrous ethanol and 0.28 kg of 25 wt% ammonia water were mixed, and 0.15 kg of ethyl orthosilicate and 0.08 kg of 3-methacryloxypropyltri(isopropenyloxy)silane were gradually added while stirring, and the mixture was heated to 55° C. and treated for 24 hours. After the treatment, the mixture was centrifuged at a speed of 5000 rpm for 5 minutes, and washed twice with water and ethanol respectively, and vacuum dried at 60° C. for 8 hours to obtain a modified compound;
[0125] S3, the modified compound prepared in step S2 is mixed and dispersed with 10 kg of 80 wt% ethanol aqueous solution, and then ground for 10 hours to prepare a slurry, the slurry is mixed with the pretreated material prepared in step S1, 0.5 kg of sodium citrate and 0.2 kg of sodium persulfate, and ultrasonicated for 1 hour at an ultrasonic power of 300 W and an ultrasonic frequency of 40 kHz to obtain a modified polyurethane coating.
[0126] Comparative Example 2
[0127] The production process of a super stain-resistant travertine-grain PVC coil is basically the same as that of Example 1, with the only difference being the preparation method of the modified polyurethane coating being different.
[0128] The preparation method of the modified polyurethane coating is as follows:
[0129] S1, 20kg polycarbonate diol, 15kg 3-ethyl heptamethyl trisiloxane and 20kg 1,6-hexamethylene diisocyanate were mixed and stirred, heated to 75°C, 0.3kg dibutyltin dilaurate was added, and after treating for 1.5 hours, the temperature was lowered to 50°C, 1kg neopentyl glycol, 1.2kg 2,2-bis(hydroxymethyl)malonic acid and 0.8kg acetone were added, and the temperature was raised to 75°C again after treating for 6 minutes, and the treatment was continued for 3 hours, and then 6kg acrylic resin was added, and the treatment was carried out at 75°C for 1.5 hours. After the reaction was completed, the temperature was lowered to 50°C, 2kg triethylamine was added, and the treatment was carried out for 40 minutes, and finally 30kg water was added and stirred for 0.5 hours to obtain a pretreated product;
[0130] S2, 0.04kg hexadecyltrimethylammonium bromide, 10kg water, 5.6kg anhydrous ethanol and 0.28kg 25wt% ammonia water were mixed, and 0.15kg ethyl orthosilicate and 0.08kg 3-methacryloxypropyltri(isopropenyloxy)silane were gradually added while stirring, and the mixture was heated to 55°C and treated for 24 hours. After the treatment, the mixture was centrifuged at a speed of 5000rpm for 5 minutes, and washed twice with water and ethanol respectively, and vacuum dried at 60°C for 8 hours to obtain a modified compound;
[0131] S3, the modified compound prepared in step S2 is mixed and dispersed with 10 kg of 80 wt% ethanol aqueous solution, and then ground for 10 hours to prepare a slurry, the slurry is mixed with the pretreated material prepared in step S1, 0.5 kg of sodium citrate and 0.2 kg of sodium persulfate, and ultrasonicated for 1 hour at an ultrasonic power of 300 W and an ultrasonic frequency of 40 kHz to obtain a modified polyurethane coating.
[0132] Comparative Example 3
[0133] The production process of a super stain-resistant travertine-grain PVC coil is basically the same as that of Example 1, with the only difference being the preparation method of the modified polyurethane coating being different.
[0134] The preparation method of the modified polyurethane coating is as follows:
[0135] S1, 20kg polycarbonate diol, 15kg 3-ethyl heptamethyl trisiloxane and 20kg 1,6-hexamethylene diisocyanate were mixed and stirred, heated to 75°C, 0.3kg dibutyltin dilaurate was added, and after treating for 1.5 hours, the temperature was lowered to 50°C, 1kg neopentyl glycol, 1.2kg 2,2-bis(hydroxymethyl)malonic acid and 0.8kg acetone were added, and the temperature was raised to 75°C again after treating for 6 minutes, and the treatment was continued for 3 hours, and then 6kg acrylic resin was added, and the treatment was carried out at 75°C for 1.5 hours. After the reaction was completed, the temperature was lowered to 50°C, 2kg triethylamine was added, and the treatment was carried out for 40 minutes, and finally 30kg water was added and stirred for 0.5 hours to obtain a pretreated product;
[0136] S2, 0.04 kg of dihexadecyl dimethyl ammonium bromide, 10 kg of water, 5.6 kg of anhydrous ethanol and 0.28 kg of 25 wt% ammonia water were mixed, and 0.15 kg of ethyl orthosilicate and 0.08 kg of γ-methacryloxypropyltrimethoxysilane were gradually added while stirring, and the mixture was heated to 55 ° C. and treated for 24 hours. After the treatment, it was centrifuged at a speed of 5000 rpm for 5 minutes, and washed twice with water and ethanol respectively, and vacuum dried at 60 ° C. for 8 hours to obtain a modified compound;
[0137] S3, the modified compound prepared in step S2 is mixed and dispersed with 10 kg of 80 wt% ethanol aqueous solution, and then ground for 10 hours to prepare a slurry, the slurry is mixed with the pretreated material prepared in step S1, 0.5 kg of sodium citrate and 0.2 kg of sodium persulfate, and ultrasonicated for 1 hour at an ultrasonic power of 300 W and an ultrasonic frequency of 40 kHz to obtain a modified polyurethane coating.
[0138] Comparative Example 4
[0139] The production process of a super stain-resistant travertine-grain PVC coil is as follows:
[0140] Step 1, 70kg of PVC resin, 5kg of calcium zinc stabilizer, 10kg of dioctyl phthalate, 0.3kg of polyethylene wax, 0.6kg of sulfur, 3kg of light calcium carbonate, 3kg of carbon black and 3kg of titanium dioxide are mixed evenly, and the mixing temperature is adjusted to 100° C. to obtain dark raw materials and light raw materials respectively;
[0141] Step 2, adding 100 kg of dark raw material and 80 kg of light raw material prepared in step 1 to two double-cone extruders respectively, extruding by conventional extrusion process, and adding the extruded raw materials together to a single screw extruder; extruding by conventional extrusion process, the extruded raw materials are cut into soft pellets with a diameter of 10 mm and a length of 3.5 mm;
[0142] Step 3, the soft pellets prepared in step 2 are immediately put into a closed heating conveyor belt to ensure that the temperature of the pellets is maintained at 158°C; the pellets quickly enter the open mill through the conveyor belt; the roller spacing of the open mill is controlled at 4mm, the temperature of the front roller is controlled at 170°C, the temperature of the rear roller is 150°C, and the speed ratio of the front and rear rollers is 0.8 to obtain refined materials, and the shear force generated by the temperature difference and speed difference of the front and rear rollers is used to form a natural and soft texture on the surface of the refined material after forming, which is very close to the natural high-end travertine; by adjusting the mass ratio of dark raw materials and light raw materials, the thickness and depth of the surface texture can be arbitrarily modulated; due to the certain proportion of water contained in the material, small holes of different sizes and depths will be formed during the extrusion and calendering process, imitating the hole structure on the surface of travertine;
[0143] Step 4: Add the refined material prepared in step 3 to 10kg of transparent PVC particles before the calender, so that the molded product also has irregular transparent points, imitating the high transparent quartz component in the travertine. The sheet molding parameters of the five-roll calender are: 1# roller temperature is controlled at 190°C and speed is 20rpm; 2# roller temperature is controlled at 190°C and speed is 22rpm; 3# roller temperature is controlled at 195°C and speed is 25rpm; 4# roller temperature is controlled at 200°C and speed is 27rpm; 5# roller temperature is controlled at 185°C and speed is 30rpm, and the calendered material is obtained;
[0144] Step 5, performing secondary vulcanization treatment on the calendered material prepared in step 4, wherein the mixed material is hot-pressed on a flat vulcanizer at 180° C. for 30 minutes, and after the secondary vulcanization treatment is completed, the mixed material is cooled to room temperature so that the edges of the holes become flat, thereby obtaining a vulcanized material;
[0145] Step 6: Apply polyurethane coating on the surface of the vulcanized material prepared in step 5, with a total coating amount of 80 g / m 2 , and then dried at 100°C at a drying speed of 12m / min to obtain a super stain-resistant travertine-grain PVC coil.
[0146] Test Example 1
[0147] Weathering test
[0148] The weather resistance test of the super stain-resistant travertine-grain PVC coils prepared in the examples and comparative examples was carried out using a xenon arc lamp weathering test chamber; a 2kW xenon lamp and 1000W / m 2 Radiation intensity, 25±2℃ test temperature, BPT80±2℃ blackboard temperature and humidity cycle from 70±5%RH to 75±5%RH; test time used to observe color changes before and after aging test.
[0149] The test results are shown in Table 1.
[0150] Table 1
[0151] Experimental protocol Aging time (h) Example 1 1852 Example 2 1653 Example 3 1781 Example 4 1790 Example 5 1721 Example 6 1985 Example 7 2096 Comparative Example 1 1752 Comparative Example 2 1597 Comparative Example 3 1602 Comparative Example 4 903
[0152] Test Example 2
[0153] Stain resistance test
[0154] Stain resistance is to evaluate whether the stains on the indoor building surface are easy to remove. The stain remover used to remove the stains during the evaluation process is non-abrasive. Stain resistance includes hydrophilic stain resistance and oleophilic stain removal.
[0155] The stain resistance of the super stain-resistant travertine-grain PVC coil prepared in the embodiments of the present invention and the comparative examples was tested. Lipstick, pencil, ballpoint pen, crayon oily stains and red wine, coffee, black tea, and green tea water-based stains were applied to the sample. After keeping it for 2 hours, a 1 kg weight was used to carry a 3M sponge to wipe back and forth 10 times. The 3M sponge was filled with water. Finally, it was washed, dried, and the stain removal effect was visually evaluated. The stain resistance was recorded according to the scoring criteria preset in Table 2.
[0156] The test results are shown in Table 3.
[0157] Table 2
[0158]
[0159] Table 3
[0160]
[0161] It can be seen from the data in Table 1 and Table 3 that the super stain-resistant travertine-grain PVC coil prepared in Example 6 has the best weather resistance and stain resistance.
[0162] The 2,2-bis(hydroxymethyl)malonic acid used in Example 1 exhibits better weather resistance and stain resistance than the alternatives used in other examples and comparative examples, which may be attributed to the fact that 2,2-bis(hydroxymethyl)malonic acid exhibits excellent weather resistance and stain resistance due to its unique molecular structure, containing two hydroxyl groups and two carboxyl groups. This structure makes 2,2-bis(hydroxymethyl)malonic acid highly active and diverse in chemical reactions. First, the two hydroxyl groups of 2,2-bis(hydroxymethyl)malonic acid enable it to participate in polycondensation reactions to form stable chemical bonds, thereby enhancing the cross-linking density and cohesion of the material, thereby improving weather resistance. Secondly, the acidity and reactivity of 2,2-bis(hydroxymethyl)malonic acid enable it to react with a variety of substances to form stable chemical bonds, which may help improve the weather resistance of the material. In terms of stain resistance, the chemical structure of 2,2-bis(hydroxymethyl)malonic acid may help to form a denser and smoother coating surface, making it more difficult for stains to adhere and easier to remove.
[0163] Compared with other silane coupling agents, 3-methacryloxypropyl tri(isopropenyloxy) silane performs better in weather resistance and stain resistance, which is mainly due to its unique chemical structure and properties. The silane monomer contains a methacryloxy group, which can copolymerize or graft with a variety of resins and polymers to form a stable chemical bond, enhancing the mechanical and electrical properties of the material. The multiple carbon-carbon double bonds in its molecule enable it to participate in free radical polymerization reactions, increase the cross-linking density of the material, and thus enhance weather resistance. In addition, the isopropoxy group of 3-methacryloxypropyl tri(isopropenyloxy) silane provides good hydrophobicity, which helps to improve the water resistance and stain resistance of the material. Therefore, the introduction of this silane monomer significantly improves the weather resistance and stain resistance of the super-fouling travertine-grain PVC coil by improving the chemical structure and physical properties of the material.
[0164] In Example 6, 3-methacryloxypropyl tri(isopropyleneoxy)silane and methacryloxypropyl tri(trimethylsiloxane)silane are compounded, which can provide better weather resistance and stain resistance than other embodiments using one silane alone. The compounding of the two silanes may produce a synergistic effect, so that the modified polyurethane coating performs well in terms of weather resistance and stain resistance. The carbon-carbon double bond contained in 3-methacryloxypropyl tri(isopropyleneoxy)silane can participate in free radical polymerization, enhance the crosslinking density of the material, and thus improve weather resistance. The trimethylsiloxane group introduced by methacryloxypropyl tri(trimethylsiloxane)silane can provide good hydrophobic properties, which helps to improve the water resistance and stain resistance of the material. The isopropyleneoxy group and carbon-carbon double bond of 3-methacryloxypropyl tri(isopropyleneoxy)silane complement the trimethylsiloxane group of methacryloxypropyl tri(trimethylsiloxane)silane in chemical structure, and work together to improve the comprehensive performance of the coating.
[0165] Compared with 2,2-bis(hydroxymethyl)malonic acid, 1,1-cyclopropyl dicarboxylic acid has an epoxy group. Due to the high tension of the three-membered ring, this group is much more active than general ethers and can undergo ring-opening reactions with a variety of reagents. This ring-opening reaction ability enables the generation of a cured product with a cross-linked structure after reacting with a multifunctional compound. This cross-linked structure enhances the chemical stability and physical strength of the material, thereby improving the material's weather resistance and stain resistance.
Claims
1. A production process for super stain-resistant travertine-grain PVC coil, characterized in that: The process is as follows, in parts by weight: Step 1, 60-80 parts of PVC resin, 4-6 parts of heat stabilizer, 8-12 parts of plasticizer, 0.2-0.4 parts of lubricant, 0.5-0.7 parts of sulfur, 2-4 parts of filler, 2-4 parts of dark pigment and 2-4 parts of light pigment are mixed evenly, and the mixing temperature is adjusted to 80-120° C. to obtain dark raw material and light raw material respectively; Step 2, adding 80-120 parts of the dark raw material and 60-100 parts of the light raw material prepared in step 1 to two double-cone extruders respectively, extruding them by conventional extrusion process, and adding the extruded raw materials together to a single screw extruder; extruding by conventional extrusion process, the extruded raw materials are cut into soft pellets with a diameter of 8-12 mm and a length of 3-4 mm; Step 3, the soft pellets prepared in step 2 are immediately put into a closed heating conveyor belt to ensure that the temperature of the pellets is maintained at 155-160°C; the pellets quickly enter the mixing mill through the conveyor belt; the roller distance of the mixing mill is controlled at 2-5mm, the temperature of the front roller is controlled at 160-180°C, the temperature of the rear roller is 140-160°C, and the speed ratio of the front and rear rollers is 0.6-0.9 to obtain refined materials; Step 4, adding 8 to 12 parts of transparent PVC particles to the refined material prepared in step 3 before the calender, and calendering to obtain a calendered material; Step 5, performing secondary vulcanization treatment on the calendered material prepared in step 4, and cooling to room temperature after the secondary vulcanization treatment is completed so that the edges of the holes become flat, thereby obtaining a vulcanized material; Step 6: Apply modified polyurethane coating on the surface of the vulcanized material prepared in step 5, with the total coating amount on both sides being 60-100 g / m 2 , and then drying at 80-110°C at a drying speed of 10-15m / min to obtain a super-fouling resistant travertine-grain PVC coil.
2. The production process of the super stain-resistant travertine-grain PVC coiled material according to claim 1, characterized in that: The dark pigment is one or two of black iron oxide, aniline black, carbon black, antimony sulfide, and red iron oxide; the light pigment is titanium white.
3. The production process of the super stain-resistant travertine-grain PVC coiled material according to claim 1, characterized in that: The heat stabilizer includes one or more of a calcium zinc stabilizer, a barium zinc stabilizer, and an organic tin stabilizer.
4. The production process of the super stain-resistant travertine-grain PVC coiled material according to claim 1, characterized in that: The plasticizer includes one or more of dioctyl phthalate, dioctyl terephthalate, trioctyl trimellitate, polypropylene adipate, epoxy soybean oil, and trioctyl trimellitate.
5. The production process of the super stain-resistant travertine-grain PVC coiled material according to claim 1, characterized in that: The lubricant includes one or more of paraffin wax, monoglyceride, and polyethylene wax; The filler includes one or more of light calcium carbonate and heavy calcium carbonate.
6. The production process of the super stain-resistant travertine-grain PVC coiled material according to claim 1, characterized in that: The calender in step 4 is a five-roll calender, and the sheet forming parameters of the five-roll calender are: the temperature of the 1# roller is controlled at 180-200°C and the speed is 18-22rpm; the temperature of the 2# roller is controlled at 180-200°C and the speed is 20-24rpm; the temperature of the 3# roller is controlled at 190-200°C and the speed is 23-27rpm; the temperature of the 4# roller is controlled at 180-220°C and the speed is 25-28rpm; the temperature of the 5# roller is controlled at 180-190°C and the speed is 28-32rpm.
7. The production process of the super stain-resistant travertine-grain PVC coiled material according to claim 1, characterized in that: The vulcanization treatment in step 5 is to hot-press the mixed material on a flat vulcanizer at 170-190° C. for 20-40 minutes.
8. The production process of the super stain-resistant travertine-grain PVC coiled material according to claim 1, characterized in that: The preparation method of the modified polyurethane coating is as follows, in parts by weight: S1. Mix and stir 18 to 22 parts of polycarbonate diol, 13 to 18 parts of 3-ethylheptamethyltrisiloxane and 18 to 22 parts of 1,6-hexamethylene diisocyanate, heat to 70 to 80°C, add 0.2 to 0.4 parts of dibutyltin dilaurate, treat for 1 to 3 hours, cool to 40 to 55°C, add 0.5 to 2 parts of neopentyl glycol, 1 to 1.5 parts of 2,2-bis(hydroxymethyl)malonic acid and 0.5 to 1 part of acetone, treat for 4 to 8 minutes, heat to 70 to 80°C again, continue to treat for 1 to 5 hours, then add 5 to 7 parts of acrylic resin, treat at 70 to 80°C for 1 to 2 hours, after the reaction is completed, cool to 40 to 60°C, add 1 to 3 parts of triethylamine, treat for 30 to 50 minutes, finally add 20 to 40 parts of water and stir for 0.1 to 1 hour to obtain a pretreated product; S2, 0.02-0.06 parts of dihexadecyl dimethyl ammonium bromide, 8-12 parts of water, 5-6 parts of anhydrous ethanol and 0.2-0.3 parts of 20-26wt% ammonia water are mixed, and while stirring, 0.1-0.2 parts of ethyl orthosilicate and 0.05-0.1 parts of 3-methacryloxypropyl tri(isopropyleneoxy)silane are gradually added, the mixture is heated to 50-60°C, and treated for 12-48 hours. After the treatment, centrifugation is performed at a speed of 3000-8000 rpm for 3-10 minutes, and washing is performed with water and ethanol for 1-3 times respectively, and vacuum drying is performed at 50-65°C for 5-10 hours to obtain a modified compound; S3, the modified compound prepared in step S2 is mixed and dispersed with 8 to 12 parts of 70 to 85 wt % ethanol aqueous solution, and then ground for 5 to 15 hours to prepare a slurry, the slurry is mixed with the pretreated material prepared in step S1, 0.4 to 0.6 parts of sodium citrate and 0.1 to 0.3 parts of sodium persulfate, and ultrasonicated for 0.5 to 2 hours at an ultrasonic power of 200 to 400 W and an ultrasonic frequency of 20 to 60 kHz to obtain a modified polyurethane coating.
9. The production process of the super stain-resistant travertine-grain PVC coiled material according to claim 1, characterized in that: The preparation method of the modified polyurethane coating is as follows, in parts by weight: S1. Mix and stir 18 to 22 parts of polycarbonate diol, 13 to 18 parts of 3-ethylheptamethyltrisiloxane and 18 to 22 parts of 1,6-hexamethylene diisocyanate, heat to 70 to 80°C, add 0.2 to 0.4 parts of dibutyltin dilaurate, treat for 1 to 3 hours, cool to 40 to 55°C, add 0.5 to 2 parts of neopentyl glycol, 1 to 1.5 parts of 2,2-bis(hydroxymethyl)malonic acid and 0.5 to 1 part of acetone, treat for 4 to 8 minutes, heat to 70 to 80°C again, continue to treat for 1 to 5 hours, then add 5 to 7 parts of acrylic resin, treat at 70 to 80°C for 1 to 2 hours, after the reaction is completed, cool to 40 to 60°C, add 1 to 3 parts of triethylamine, treat for 30 to 50 minutes, finally add 20 to 40 parts of water and stir for 0.1 to 1 hour to obtain a pretreated product; S2, 0.02-0.06 parts of dihexadecyl dimethyl ammonium bromide, 8-12 parts of water, 5-6 parts of anhydrous ethanol and 0.2-0.3 parts of 20-26wt% ammonia water are mixed, and while stirring, 0.1-0.2 parts of ethyl orthosilicate and 0.03-0.05 parts of 3-methacryloxypropyl tris(isopropyleneoxy)silane and 0.03-0.05 parts of methacryloxypropyl tris(trimethylsiloxy)silane are gradually added, and the mixture is heated to 50-60°C and treated for 12-48 hours. After the treatment, the mixture is centrifuged at a speed of 3000-8000 rpm for 3-10 minutes, and washed with water and ethanol for 1-3 times respectively, and vacuum dried at 50-65°C for 5-10 hours to obtain a modified compound; S3, the modified compound prepared in step S2 is mixed and dispersed with 8 to 12 parts of 70 to 85 wt % ethanol aqueous solution, and then ground for 5 to 15 hours to prepare a slurry, the slurry is mixed with the pretreated material prepared in step S1, 0.4 to 0.6 parts of sodium citrate and 0.1 to 0.3 parts of sodium persulfate, and ultrasonicated for 0.5 to 2 hours at an ultrasonic power of 200 to 400 W and an ultrasonic frequency of 20 to 60 kHz to obtain a modified polyurethane coating.
10. A super stain-resistant travertine-grain PVC coil, characterized in that: The invention is prepared by the production process described in any one of claims 1 to 9.
Citation Information
Patent Citations
Polyvinyl chloride waterproof roll material and preparation method thereof
CN106554581A